THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDES AND LIFESTYLE ON THE FINANCIAL MANAGEMENT CAPABILITY OF STIE SBI YOGYAKARTA STUDENTS - Indah Lestari, Nur Siti; Albertus, Redy Herinanto; Murdo, Ilham Tri (Universitas Pembinaan Masyarakat Indonesia, 2024)
This study aims to examine the effect of financial literacy, financial attitudes and lifestyle on the financial management skills of STIE SBI Yogyakarta students. The research method used is quantitative method, with multiple linear regression analysis. The tests used to test the hypothesis are t test, f test, and coefficient of determination test. The data collection technique used a questionnaire with 214 respondents. The results of this study indicate that financial literacy, financial attitudes, and lifestyle have a positive and significant effect on the financial management skills of STIE SBI Yogyakarta students partially. Simultaneously financial literacy, financial attitudes, and lifestyle have a positive and significant effect on the financial management skills of STIE SBI Yogyakarta students, namely 0.477 or 47.7% and the remaining 52.3% is influenced by other variables not examined by researchers. JEL Classification: M41, M10